Antibacterial And Antifungal Activity of Solanum Melongena L. (Eggplant) Leaf Extract on Selected Oral Pathogens - Elazegui, Carmela; Arquiza, Milger Joy; Abacan, Katrina Joyce; Cameros, Trizia Marie; Lapis, Joana Patricia; Flores, Katrina Joyce; Mercado, Giovani; Ramos, Rowena; Subido Jr. , Herminiano; Tajud, Alexa Eline (12th International Scholars Conference 2025, 2026)
This study investigates the antibacterial and antifungal activities of Solanum melongena L. (eggplant) leaf extract against oral pathogens Streptococcus mutans and Candida albicans. Phytochemical analysis identified secondary metabolites such as sterols, triterpenes, flavonoids, alkaloids, saponins, glycosides, and tannins, which are known for their antimicrobial and antioxidant properties. The Kirby-Bauer test was used to assess the inhibitory effects of Solanum melongena L. leaf extract, normal saline solution (NSS), and chlorhexidine against S. mutans and C. albicans. Statistical analysis, including one-way ANOVA, assessed antibacterial activity at concentrations of 50% 75%, and 100%. Results showed that there is no antifungal activity for the eggplant leaf extract, chlorhexidine, or NSS against C. albicans as none of them showed any zone of inhibition. However, the eggplant leaf extract showed concentration-dependent antibacterial activity against S. mutans, with higher concentrations producing stronger inhibitory effects. Despite the effectiveness of the eggplant leaf extract, it was proven that chlorhexidine is still more effective against S. mutans. These findings suggest potential applications of Solanum melongena L. leaf extract as a natural antibacterial agent in oral care, with further studies needed to improve its formulation for broader antimicrobial effectiveness.